2023
DOI: 10.3390/diagnostics13040746
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Blood-Cell-Count-Derived and CRP-Derived Inflammatory Indices of COVID-19 Patients

Abstract: The aim of the study was to investigate the serial changes in inflammatory indices derived from blood cell counts and C-reactive protein (CRP) levels in COVID-19 patients with good and poor outcomes. We retrospectively analyzed the serial changes in the inflammatory indices in 169 COVID-19 patients. Comparative analyses were performed on the first and last days of a hospital stay or death and serially from day 1 to day 30 from the symptom onset. On admission, non-survivors had higher CRP to lymphocytes ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The study design was prospective in three studies ( 50 , 67 , 68 ), unclear in one ( 66 ), and retrospective in the remaining 36 ( 21 , 36 49 , 51 65 , 69 74 ). The clinical endpoints included mortality in 19 studies ( 36 , 37 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 61 , 65 , 66 , 68 , 73 ), and measures of severe disease as follows: disease severity based on existing guidelines in eight ( 42 , 44 , 63 , 64 , 67 , 70 , 72 , 74 ), transfer to the intensive care unit (ICU) in eight ( 38 , 40 , 45 , 50 , 53 , 62 , 68 , 69 ), invasive mechanical ventilation in two ( 46 , 52 ), disease progression in two ( 57 , 71 ), prolonged hospital stay in one ( 21 ), intubation in one ( 37 ), deep vein thrombosis in one ( 54 ), acute pulmonary embolism in one ( 54 ), and acute limb ischemia in one ( 39 ). All studies reported the SII on hospital admission.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design was prospective in three studies ( 50 , 67 , 68 ), unclear in one ( 66 ), and retrospective in the remaining 36 ( 21 , 36 49 , 51 65 , 69 74 ). The clinical endpoints included mortality in 19 studies ( 36 , 37 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 61 , 65 , 66 , 68 , 73 ), and measures of severe disease as follows: disease severity based on existing guidelines in eight ( 42 , 44 , 63 , 64 , 67 , 70 , 72 , 74 ), transfer to the intensive care unit (ICU) in eight ( 38 , 40 , 45 , 50 , 53 , 62 , 68 , 69 ), invasive mechanical ventilation in two ( 46 , 52 ), disease progression in two ( 57 , 71 ), prolonged hospital stay in one ( 21 ), intubation in one ( 37 ), deep vein thrombosis in one ( 54 ), acute pulmonary embolism in one ( 54 ), and acute limb ischemia in one ( 39 ). All studies reported the SII on hospital admission.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-nine studies (with 45 patient groups) reported the SII in 19,352 patients (mean age 61 years, 55% males) with a non-severe disease/survivor status and 5,524 patients (mean age 69 years, 60% males) with a severe disease/non-survivor status. Twenty-three studies were conducted in Asia ( 36 , 38 , 40 42 , 48 51 , 57 , 59 , 62 68 , 70 74 ), eleven in Europe ( 21 , 39 , 43 , 44 , 47 , 55 , 56 , 58 , 60 , 61 , 69 ), four in America ( 37 , 45 , 46 , 52 ), and one in Africa ( 53 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, upon admission, individuals who did not survive exhibited elevated CLR and MII values compared to those who survived. However, at the point of discharge or death, the most notable distinctions were observed concerning the NLR, Systemic Inflammation Response Index (SIRI), and MII [ 3 ]. Consistent with the literature, in this study, the MII value was significantly higher upon admission and on the third day of hospitalization in the severe disease group (p=0.020 and p=0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The complete blood count is a cost-effective, readily available, and efficient method for assessing inflammation in the early detection and prognosis of diseases. The dynamic nature of inflammation in COVID-19 is vital and has a direct correlation with physiological parameters [ 3 ]. Inflammatory biomarkers play a crucial role in understanding and monitoring the progression of various diseases, including COVID-19.…”
Section: Introductionmentioning
confidence: 99%